Efficient transformation of germinating Neurospora conidia using total nuclear DNA fragments. - J. C. Wootten; M. J. Fraser; A. J. Baron (Fungal Genetics Reports, 1980)
Efficient transformation of germinating Neurospora conidia using total nuclear DNA fragments.